Local ecological knowledge also ‘comes from books’: cultural change, landscape transformation and conservation of biodiversity in two protected areas in Portugal - Frazão-Moreira, Amélia (2011)
Artigo resultante de uma comunicação oral apresentada na 10th European Association of Social Anthropologists (EASA) Conference em Agosto de 2008, na Eslovénia. Tema central: Experiencing diversity and mutuality. Painel Societies and protected areas